A long-term evaluation of recent Hungarian pension reforms - Christoph Freudenberg; Tamás Berki; Ádám Reiff (Magyar Nemzeti Bank, 2016)
This paper studies the effect of Hungarian pension reforms between 2009-2012 on the adequacy and long-term fiscal stability of the Hungarian public pension system. For the adequacy analysis, we use a micro simulation model to project future initial pension levels relative to future gross wages. For the analysis of fiscal stability, we use a generational accounting-based macro model to forecast future yearly cash balances and calculate implicit pension liability (IPL) indicators. We find that major recent reforms have stabilized the public pension system until around 2035, but after this, mainly due to unfavorable demographic developments, we project increasing deficits that reach about 4% of GDP by 2060.
Keywords: H55; 330; Pension reforms; Sustainability of pension systems; Micro simulation